2021
DOI: 10.1109/jstars.2021.3118398
|View full text |Cite
|
Sign up to set email alerts
|

GNSS-IR Model of Sea Level Height Estimation Combining Variational Mode Decomposition

Abstract: The Global Navigation Satellite System-Reflections (GNSS-R) signal has been confirmed to be useful for retrieving sea level height. At present, the GNSS-Interferometric Reflectometry (GNSS-IR) technology based on the least square method to process signal-to-noise ratio (SNR) data is restricted by the satellite elevation angle in terms of accuracy and stability. This paper proposes a new GNSS-IR model combining variational mode decomposition (VMD) for sea level height estimation. VMD is used to decompose the SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The requirement of GNSS-IR for sea level measurement is to record both the direct GNSS signals and the GNSS reflected signals that are reflected off from the sea surface. There have been numerous different methods and techniques for using the GNSS-reflected signals for sea level observations and lake level monitoring from ground-based surfaces [1], [3], [5], [6], [7], [8].…”
Section: Identification Of Optimum Parameters For Snr Data Analysismentioning
confidence: 99%
“…The requirement of GNSS-IR for sea level measurement is to record both the direct GNSS signals and the GNSS reflected signals that are reflected off from the sea surface. There have been numerous different methods and techniques for using the GNSS-reflected signals for sea level observations and lake level monitoring from ground-based surfaces [1], [3], [5], [6], [7], [8].…”
Section: Identification Of Optimum Parameters For Snr Data Analysismentioning
confidence: 99%
“…This method can obtain instantaneous RHs with high temporal resolution. Hu et al proposed a variational mode decomposition method and improved the Burg algorithm for SNR data spectrum analysis, and about a 5 cm precision was reached by adopting GTGU station data [20,21]. Although there are many methods available to extract the oscillation frequency of SNR data, the LSP is the most widely applied to GNSS-IR altimetry due to better spectrum analysis of non-uniform sampling signals.…”
Section: Introductionmentioning
confidence: 99%
“…proposed a new GNSS‐IR sea level estimation model combined with Variational Mode Decomposition (VMD). The experimental results showed that RMSE and R of the new model are 4.86 cm and 0.97, respectively (Y. Hu et al., 2021). In 2021, Liu et al.…”
Section: Introductionmentioning
confidence: 99%